2022
DOI: 10.3389/fnagi.2022.1023195
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among peripheral blood markers, white matter hyperintensity, and cognitive function in patients with non-disabling ischemic cerebrovascular events

Abstract: BackgroundBoth inflammation and cerebral white matter injury are closely associated with vascular cognitive impairment (VCI). The aim of this study was to analyze the correlation between peripheral serological markers, white matter injury, and cognitive function in patients with non-disabling ischemic cerebrovascular events (NICE); to identify potential biological markers for the diagnosis and prediction of VCI; and to provide a basis for the early diagnosis and intervention of VCI.MethodsWe collected clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The “inflammatory mechanism” hypothesis, widely accepted as the dominant theory of VCI, has a crucial function in the processes of degradation and regeneration of myelin 4 . Our prior clinical and animal studies on VCI have consistently shown the crucial involvement of microglial activation and concomitant neuroinflammation in the progression of WMLs and cognitive dysfunction 5,6 . Moreover, our study has shown that distinct inhibition of microglial activation and neuroinflammatory response in the hippocampus leads to differential improvement in myelin repair and ultimately enhances cognitive function in VCI mice 7 .…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The “inflammatory mechanism” hypothesis, widely accepted as the dominant theory of VCI, has a crucial function in the processes of degradation and regeneration of myelin 4 . Our prior clinical and animal studies on VCI have consistently shown the crucial involvement of microglial activation and concomitant neuroinflammation in the progression of WMLs and cognitive dysfunction 5,6 . Moreover, our study has shown that distinct inhibition of microglial activation and neuroinflammatory response in the hippocampus leads to differential improvement in myelin repair and ultimately enhances cognitive function in VCI mice 7 .…”
Section: Introductionsupporting
confidence: 52%
“… 4 Our prior clinical and animal studies on VCI have consistently shown the crucial involvement of microglial activation and concomitant neuroinflammation in the progression of WMLs and cognitive dysfunction. 5 , 6 Moreover, our study has shown that distinct inhibition of microglial activation and neuroinflammatory response in the hippocampus leads to differential improvement in myelin repair and ultimately enhances cognitive function in VCI mice. 7 Neuroinflammation has the potential to cause WMLs, which are responsible for cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 75%
“…That is, whereas both HCV and albumin correlated with serum markers of liver function (i.e., aspartate transaminase, prealbumin; note, although prealbumin is sometimes considered a nutritional marker, Quest Diagnostics, states that "prealbumin is decreased in liver disease"), only albumin additionally correlated with hematological markers (i.e., lower red blood cell count, lower hemoglobin, lower hematocrit, and higher red cell distribution width). These relations between albumin and altered hemodynamic pro les have previously been reported [111] and may re ect cardiovascular dysfunction [112][113][114][115][116][117].…”
Section: Discussionmentioning
confidence: 65%
“…White matter hyperintensities (WMHs), recent small subcortical infarcts, cerebral microbleeds and perivascular spaces are all unique neuroimaging markers of VCI, in which WMHs are more able to reflect white matter injury [ 7 ]. In our prior investigation, we established a positive correlation between the severity of WMHs and the extent of cognitive decline in individuals afflicted with CVD [ 8 ].…”
Section: Introductionmentioning
confidence: 99%